2016
DOI: 10.1016/j.celrep.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Fin1-PP1 Helps Clear Spindle Assembly Checkpoint Protein Bub1 from Kinetochores in Anaphase

Abstract: The spindle assembly checkpoint (SAC) monitors chromosome attachment defects and the assembly of SAC proteins at kinetochores is essential for its activation, but the SAC disassembly process remains unknown. We found that deletion of a 14-3-3 protein, Bmh1, or hyper-activation of FEAR (Cdc14 Early Anaphase Release) allows premature SAC silencing in budding yeast, which depends on a kinetochore protein Fin1 that forms a complex with protein phosphatase PP1. Previous works suggest that FEAR-dependent Fin1 dephos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…FEAR-mediated Cdc14 release leads to Fin1 dephosphorylation and kinetochore recruitment of Fin1-PP1, which clears SAC protein Bub1 from the kinetochore. The results from phospho-deficient fin1 mutants (fin1-5A) support the expected consequence of Fin1 dephosphorylation [77,86]. Therefore, Cdc14 phosphatase also regulates Ipl1/PP1 balance at the kinetochore through Fin1 dephosphorylation during anaphase, although the biological significance of this regulation is not fully understood yet (Figure 3).…”
Section: Phosphatase Cdc14mentioning
confidence: 54%
See 2 more Smart Citations
“…FEAR-mediated Cdc14 release leads to Fin1 dephosphorylation and kinetochore recruitment of Fin1-PP1, which clears SAC protein Bub1 from the kinetochore. The results from phospho-deficient fin1 mutants (fin1-5A) support the expected consequence of Fin1 dephosphorylation [77,86]. Therefore, Cdc14 phosphatase also regulates Ipl1/PP1 balance at the kinetochore through Fin1 dephosphorylation during anaphase, although the biological significance of this regulation is not fully understood yet (Figure 3).…”
Section: Phosphatase Cdc14mentioning
confidence: 54%
“…cdc55∆ mutant cells show premature release of Cdc14, which allows the dephosphorylating of CDK substrates, including the CPC component Sli15. We found that Cdc55 is required for efficient cell cycle delay in response to tensionless attachment [77]. It will be interesting to examine the Ipl1 kinetochore localization in cdc55 mutant cells at metaphase to clarify if the dysfunction of PP2A Cdc55 compromises CPC kinetochore localization.…”
Section: Protein Phosphatase 2a (Pp2a)mentioning
confidence: 87%
See 1 more Smart Citation
“…Cdc13 binds to telomeres and protects chromosome ends 30 . In cdc13-1 mutants incubated at non-permissive temperatures, unprotected telomeres activate the DNA damage checkpoint to arrest cells in pre-anaphase with established chromosome bipolar attachment 31 , 32 . To follow the process of chromosome bipolar attachment, WT and dam1-3A mutant cells with Mtw1-GFP and Tub1-mCherry were arrested in G 1 phase and then released into 34 °C medium containing nocodazole for 2 hr.…”
Section: Resultsmentioning
confidence: 99%
“…The association of PP1 with Spc105 is essential for the SAC silencing, and mutation of the PP1 binding site in Spc105 protein results in lethality due to the failure of SAC silencing 35 . Although Fin1 is also responsible kinetochore recruitment of PP1, this function is not essential for SAC silencing as fin1 ∆ deletion mutants are viable 32 , 36 , 37 . It will be our future interest to investigate the role of Spc105- or Fin1-associated PP1 in Dam1 dephosphorylation.…”
Section: Discussionmentioning
confidence: 99%